Non-Muslim Discourse in Abdullah Saeed's Perspective - Yasmar, Renti; Syakir Hidayat, Ahmad Fadhel; Sumbulah, Umi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study specifically looks at Abdullah Saeed as a minority Muslim scholar whose topic specifically addresses non-Muslim discourses in the Qur'an. with the aim of seeing Abdullah Saeed's construct of thought in interpreting the Qur'an and to see how Abdullah Saeed interprets non-Muslim verses in the Qur'an. Meanwhile, in the research process, the researcher uses the library research method which is descriptive-analytical which functions to interpret data with a historical- critical approach. In general, there are two sources of data, namely primary and secondary. Primary data sources will be seen from the works of Abdullah Saeed. As for the secondary data from several documents and other related articles. Data analysis used three techniques of descriptive analysis, taxonomic analysis and interpretive analysis. The results of this discussion are divided into 3 things. The first is the presentation of Abdullah Saeed's socio-historical background. Second, the exposure about Abdullah Saeed's contextualist approach who is elaborative, argumentative and comprehensive in interpreting the Koran. Third. non-Muslim discourse in this regard, Abdullah Saeed reviews the doctrine of the crucifixion of Isa in the Koran and freedom of religion and interfaith brotherhood in the verses of the Koran; Abdullah Saeed highlighted the apostasy law as the basis for freedom of religion